Does tinnitus, hearing asymmetry, or hearing loss predispose to occupational injury risk?. (February 2015) - Cantley, Linda F.; Galusha, Deron; Cullen, Mark R.; Dixon-Ernst, Christine; Tessier-Sherman, Baylah; Slade, Martin D.; Rabinowitz, Peter M.; Neitzel, Richard L.
Abstract: Objective: To determine the relative contributions of tinnitus, asymmetrical hearing loss, low frequency hearing loss (pure tone average of 0.5, 1, 2, 3 kHz; PTA.5123 ), or high frequency hearing loss (pure tone average of 4, 6 kHz; PTA46 ), to acute injury risk among a cohort of production and maintenance workers at six aluminum manufacturing plants, adjusting for ambient noise exposure and other recognized predictors of injury risk. Design: Retrospective analysis. Study sample: The study considered 9920 workers employed during 2003 to 2008. The cohort consisted of 8818 workers (89%) whose complete records were available. Results: Adjusting for noise exposure and other recognized injury predictors, a 25% increased acute injury risk was observed among workers with a history of tinnitus in conjunction with high-frequency hearing loss (PTA46 ). Low frequency hearing loss may be associated with minor, yet less serious, injury risk. We did not find evidence that asymmetry contributes to injury risk. Conclusion: These results provide evidence that tinnitus, combined with high-frequency hearing loss, may pose an important safety threat to workers, especially those who work in high-noise exposed environments. These at risk workers may require careful examination of their communication and hearing protection needs.